A Study for Determining the Inclination of the Occlusal Plane from the Mandibular Functional Trajectory - Kazuhiro Ikeda; Shuichiro Yamashita (Hindawi Limited, 2022)
Background. During the fabrication of prostheses, the putative occlusal plane is generally determined based on morphological criteria such as Camper's plane. There is a possibility that morphological indexes deviate from their original positions over time. The current study investigated whether functional indexes could be used to determine occlusal planes instead of morphological indexes. Objectives. The objectives of the present study were to investigate the relationship between the maxillary occlusal plane and mandibular functional trajectory and to consider a method for reconstructing a lost occlusal plane based on functional trajectories. Methods. Thirteen healthy dentulous individuals were recruited for the study. Using a jaw motion tracking device with 6-degrees of freedom, the trajectories of the mandibular first molar and incisor during masticatory movement or tapping movements were measured. Results. The closing angle of the mandibular first molar to the maxillary occlusal plane was converged and averaged 74.1° just below the intercuspal position, which is the terminal position of masticatory movement. This angle was positively correlated with the closing angle of the incisal point during tapping movement. The regression equation obtained was y = 0.37x + 45.99, where x was the closing angle of tapping movement and y was the closing angle of masticatory movement. Conclusions. It was suggested that when determining lost occlusal plane, the occlusal plane can be derived using the closing angle of the incisal point during tapping movement.